2000
DOI: 10.1034/j.1399-6576.2000.440921.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic stability during moderate hypotensive anaesthesia for spinal surgery. A comparison between desflurane and isoflurane

Abstract: Desflurane, administered via a semi-closed circuit at 1 l x min(-1) fresh gas flow, maintained better haemodynamic stability in spinal surgery requiring moderate arterial hypotension than isoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Similar to our results, Beausier et al concluded that desflurane was better than isoflurane for establishment of hypotension during spinal surgery. [20] Reason for lesser decrease in blood pressure and QTd increase in desflurane group may be related to its sympathetic activity.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to our results, Beausier et al concluded that desflurane was better than isoflurane for establishment of hypotension during spinal surgery. [20] Reason for lesser decrease in blood pressure and QTd increase in desflurane group may be related to its sympathetic activity.…”
Section: Discussionmentioning
confidence: 97%
“…Systolic BP was 21.2% (9.5–41.7) of time outside the range 80-100 mmHg with isoflurane as compared to 5.1% (0.6–10.3) with desflurane ( P < 0.01). [41]…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Desflurane is characterized by rapid elimination and early recovery from anesthesia [3]. Although desflurane elicits sympathetic activation, hypertension, and tachycardia when its inspired concentration exceeds 1.0 minimum alveolar concentration (MAC) [4], it provides faster and tighter hemodynamic control than other volatile agents at lower than 1.0 MAC [5,6], suggesting that desflurane might be safely used during anesthesia for resection of pheochromocytomas. However, there have been only a few reports describing anesthesia with desflurane in patients undergoing pheochromocytoma surgery [7][8][9].…”
Section: Introductionmentioning
confidence: 99%